2022
DOI: 10.1111/ctr.14790
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to third SARS‐CoV‐2 vaccination in seronegative kidney transplant recipients: Possible improvement by mycophenolate mofetil reduction

Abstract: Modification of vaccination strategies is necessary to improve the immune response to SARS‐CoV‐2 vaccination in kidney transplant recipients (KTRs). This multicenter observational study analyzed the effects of the third SARS‐CoV‐2 vaccination in previously seronegative KTRs with the focus on temporary mycophenolate mofetil (MMF) dose reduction within propensity matched KTRs. 56 out of 174 (32%) previously seronegative KTRs became seropositive after the third vaccination with only three KTRs developing neutrali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Nonetheless, the de novo DSA formation and increases in the MFI of preexisting DSA at both t1 and t2 suggest an association between MPA withdrawal and enhanced alloimmune response. Considering possible options to enhance patients’ safety for future approaches of MPA withdrawal for immunocompromised nonresponders, Kantauskaite et al 12 have shown that an MPA dosage reduction by 25% to 50% before a third vaccination led to an enhanced immune response in 24 KTRs. Regele et al, 34 on the other hand, showed that a shorter MPA withdrawal period 2 wk perivaccination failed to enhance vaccine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the de novo DSA formation and increases in the MFI of preexisting DSA at both t1 and t2 suggest an association between MPA withdrawal and enhanced alloimmune response. Considering possible options to enhance patients’ safety for future approaches of MPA withdrawal for immunocompromised nonresponders, Kantauskaite et al 12 have shown that an MPA dosage reduction by 25% to 50% before a third vaccination led to an enhanced immune response in 24 KTRs. Regele et al, 34 on the other hand, showed that a shorter MPA withdrawal period 2 wk perivaccination failed to enhance vaccine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have analyzed the effects of an additional COVID-19 vaccination during short-term MPA withdrawal (4–6 wk) and have demonstrated significantly higher seroconversion rates than patients on continued immunosuppressive maintenance therapy. 9-12…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we did not find a statistically significant association between the type of immunosuppressive treatment and non-response. Nevertheless, significant correlation with seroconversion in kidney transplant recipients who discontinued treatment with an antimetabolite prior to a third vaccination had been observed [ 28 , 30 , 31 ]. Osmanodja et al found that younger age, higher BMI, higher transplant age, higher eGFR, and higher hemoglobin levels were associated with improved serological response after a third vaccination [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet attempts have been made to provide an overview. In case of baseline serum creatinine levels, except for one study [ 17 ], all other reports indicated trends of lower serum creatinine values in seroresponders than in non-responders [ 53 , 58 , 61 ], with some of them reaching significance [ 18 , 21 , 60 ]. Vintage on RRT, however, tended to be longer in responders in all [ 17 , 21 , 32 , 53 , 61 ], but one [ 13 ] study.…”
Section: Resultsmentioning
confidence: 99%